2019
DOI: 10.1016/j.mineng.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Urban mining of precious metals via oxidizing copper smelting

Abstract: Recycling of precious metals from end-of-life electronics is a key factor for sustainable and efficient raw material usage. Simultaneously with the depletion of natural ore resources, the urban mines are storing increasing amounts of valuable and, more importantly, rare metals. To fulfill the targets of sustainability and move towards circular economy, the liberation of these valuables from wastes back to production and use needs to be improved. This study investigates the recoveries and behavior of gold, silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 36 publications
1
24
3
1
Order By: Relevance
“…48 It is, therefore, evident that, in the oxidising process steps, platinum also dissolves as PtO 0.5 in copper-containing iron silicate slags used in secondary copper smelting and refining. Thus, the recent experimentally determined concentrations of platinum in metallurgical slags, 33,34,36 as well as the relationships obtained for platinum distributions between the copper and the slag, were distorted by the detection limits of the analytical techniques used in the phase analyses, as considered earlier. 34 In addition, the chemical dissolution of platinum in the slag in this study is lower than stated in our recent papers, 34,36 where concentrations were reported as upper limits only.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…48 It is, therefore, evident that, in the oxidising process steps, platinum also dissolves as PtO 0.5 in copper-containing iron silicate slags used in secondary copper smelting and refining. Thus, the recent experimentally determined concentrations of platinum in metallurgical slags, 33,34,36 as well as the relationships obtained for platinum distributions between the copper and the slag, were distorted by the detection limits of the analytical techniques used in the phase analyses, as considered earlier. 34 In addition, the chemical dissolution of platinum in the slag in this study is lower than stated in our recent papers, 34,36 where concentrations were reported as upper limits only.…”
Section: Discussionmentioning
confidence: 95%
“…This will allow us to verify the dissolution mechanism investigated earlier in copper-saturated slag systems of WEEE smelting (waste electric and electronic equipment) for dilute platinum concentrations. [32][33][34]…”
Section: Background Informationmentioning
confidence: 99%
“…This conclusion regarding dissolution as neutral, elemental species should trations of tellurium in matte-slag system, adopted from Sukhomlinov et al [24], are shown for comparison be reliable in the sense that the concentrations of tellurium in ISA slags and copper alloy in all experimental conditions were well above the detection limits of LA-ICP-MS and EPMA, respectively. Thus, the calculated distribution coefficient values represent actual coefficients, not minimum ones, such as reported by us for platinum, for example [34]. In oxidizing conditions, 5 wt% potassium oxide in the slag notably increased the deportment of tellurium into the copper alloy, where it can be recovered in later process stages by anode slime treatment.…”
Section: Distribution Behavior Of Telluriummentioning
confidence: 63%
“…The drop-quench technique employed in this study is already relatively widely used in phase equilibria studies [23,24], and nowadays also in minor element investigations [25,26]. The critical steps of the technique include (1) sample precursor preparation, (2) equilibration-quenching experiments and (3) EPMA measurements.…”
Section: Methodsmentioning
confidence: 99%